An advanced time-dependent collisional-radiative model of helium plasma discharges. (25th September 2017) - Claustre, J; Boukandou-Mombo, C; Margot, J; Matte, J-P; Vidal, F
Abstract: A new spatially averaged time-dependent collisional-radiative model for helium plasmas, coupled to the electron Boltzmann equation (EBE), has been developed. Its main novelties are: (1) full time dependence for both the multi-species kinetics and the EBE. It is shown that this is necessary to correctly simulate discharges where the parameters vary on nanoseconds-microsecond timescales. (2) All electron processes are accounted for accurately. In particular, for the various ionization and recombination processes, free electrons are added or removed at the appropriate energy, with the appropriate interpolation on the energy grid. (3) The energy dependence of the electron loss by ambipolar diffusion is taken into account approximately. (4) All of the processes which are known to be important in helium discharges for pressure P ≤ 760 Torr are included, and 42 energy levels up to n = 6, where n is the main quantum number, are taken into account. Atomic and molecular ions, as well as excimers, are also included. (5) The gas temperature is calculated self-consistently. The model is validated through comparisons with known numerical steady-state results of Santos et al (2014 J. Phys. D. 47 265201) which they compared to their experimental results, and good agreement is obtained for their measured quantities. It is then applied to post-discharge decay cases with very short power decay times. The time evolution of the population densities and reaction rates are analyzed in detail with emphasis on the observed large increase of the metastable density.